2012
DOI: 10.1021/jo302039n
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II)- and Palladium(II)-Catalyzed Enantioselective Claisen Rearrangement of Allyloxy- and Propargyloxy-Indoles to Quaternary Oxindoles and Spirocyclic Lactones

Abstract: In this paper, a strategy to obtain highly enantioselective catalysts for the Claisen rearrangement of allyloxy- and propargyloxy-indoles is outlined. Ultimately, copper BOX and palladium BINAP or PHOX catalysts were discovered as superior in catalyzing Claisen rearrangements of allyloxy- or proparyloxy-substituted indoles to generate oxindoles bearing allyl- or allenyl-substituted quaternary centers. This method proved to be tolerant of a broad range of functional groups. Tandem reactions of the silyl-allene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 102 publications
0
23
0
Order By: Relevance
“…Notably,w hen using substrates with an electron-enriched aryl R 3 group (e.g., 3ae, 3ai, 3ak, 3am,a nd 3an), some extent of the erosion of chirality transfer could be observedf or the formation of the correspondingp roducts( entries 6, 10, 12, 14, and 15), and this might be due to the competitive nonconcerted rearrangement arising from the C1'ÀOb ond heterolytic cleavage facilitated by the electronically enriched property of the R 3 group. In addition, two additional examples using 3ao and 3ap (entries [16][17] with an extended conjugated system (R 3 = (E)-styryl and phenylacetylenyl)w ere evaluated, and the expected rearrangementp roducts 4ao (92 %y ield, 88 % ee)a nd 4ap (83 %y ield, 86 % ee)w ere afforded, giving the potential of late-stagefunctionalization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably,w hen using substrates with an electron-enriched aryl R 3 group (e.g., 3ae, 3ai, 3ak, 3am,a nd 3an), some extent of the erosion of chirality transfer could be observedf or the formation of the correspondingp roducts( entries 6, 10, 12, 14, and 15), and this might be due to the competitive nonconcerted rearrangement arising from the C1'ÀOb ond heterolytic cleavage facilitated by the electronically enriched property of the R 3 group. In addition, two additional examples using 3ao and 3ap (entries [16][17] with an extended conjugated system (R 3 = (E)-styryl and phenylacetylenyl)w ere evaluated, and the expected rearrangementp roducts 4ao (92 %y ield, 88 % ee)a nd 4ap (83 %y ield, 86 % ee)w ere afforded, giving the potential of late-stagefunctionalization.…”
Section: Resultsmentioning
confidence: 99%
“…[10] Stimulated by the topological inspiration of allylic aryl ether subunits embedded in such structurally unique nine-membered heterocycles (A)r esulting from above designed [4+ +5] annulation, im-Scheme1.Previousknown asymmetriccatalytic modes driven by aromatization of o-QMs, andour design for the [4+ +5] annulation and its tandem rearrangement. portantly,w ed isclose an unprecedented tandemr earrangement reaction( Scheme 1), mainly involving ah ighly stereoselective aromatic Claisen rearrangement [11] wherein an ovel approach to the enantioselective construction of all-carbon quaternary stereogenic centers contained in chiral phenol-functionalized homoallylic alcohols (B) [12][13][14] is revealed through a tracelessc hirality transfer strategy.N otably,a mong numerous investigations on the asymmetric creation of all-carbon quaternary centers through aliphatic Claisen rearrangements, [15] there are only af ew reports based on asymmetrica romatic Claisen rearrangements typically using aryl allyl ethers, [16,17] mostly because of the high activation barrier accompanying dearomatization for in situ generation of sterically congested quaternary carbon centers. Herein, we report our resultsont his subject.…”
mentioning
confidence: 99%
“…2 In fact, various synthetic routes for these oxindoles are described in the literature. [3][4][5][6][7][8][9] Especially, tandem reduction-lactamization, which uses dimethyl or diethyl 2-alkyl-2-(2-nitrophenyl)malonates, is considered one of the most efficient method for preparing these oxindoles. For example, Acheson and co-workers reported that Raney nickel catalyzed hydrogenation of the nitro group of the diethyl 2-methyl-2-(2-nitrophenyl)malonate produces oxindole 3.…”
Section: Introductionmentioning
confidence: 99%
“…Several synthetic approaches have been proposed to date in the literature. A few notable examples are: (i) Pd‐catalysed asymmetric allylic alkylation; (ii) Black rearrangement approach; (iii) PET‐catalysed (PET = photoinduced electron transfer) [3+2] reactions; (iv) Cu‐ and Pd‐catalysed Claisen rearrangement of allyloxy‐ and propargyloxy‐indoles; (v) intramolecular dehydrogenative coupling; (vi) Nd III – N , N′ ‐dioxide‐mediated synthesis; (vii) Ni‐catalysed Heck cyclization approach; (viii) Ru‐catalysed C–H functionalization; (ix) dearomatization approach, and so on.…”
Section: Introductionmentioning
confidence: 99%